Sistem Monitoring Daya Sel Surya Pada Mobil Listrik Surya Unisla Berbasis IoT - Bachri, Affan; Laksono, Arief Budi; Susilo, Purnomo Hadi; Hartantyo, Sugeng Dwi; Rohman, Mohammad Ainur (Jurnal Teknik Elektro dan Informatika, 2025)
In this study, Unisla's solar electric vehicles uses five 100Wp solar panels assembled in series so that it has a total power of 500Wp. The design of this solar cell power monitoring system uses ESP32 as a microcontroller with the concept of Internet of Things (IoT) so that the device can be connected to the internet in real-time. The sensors used to read the current and voltage flowing from the solar panel are the ACS712 sensor and the voltage sensor is a voltage divider circuit made from resistors with R1 66100 Ohm and R2 3200 Ohm values respectively. Of the 10 test samples, the average error value of the voltage sensor used had a fairly good accuracy, with an average error of only 0.301%. This shows that the measurement difference between the sensor and the multimeter is relatively small. Meanwhile, the measurement difference between the ACS712 sensor and the power supply is very small, ranging from 0.01 to 0.02 Amperes with an average error of 0.01%. This shows that the measurement deviation of the ACS712 sensor compared to the reference value is very small, making it reliable for current measurement applications. The power monitoring tool developed was successfully implemented on Unisla Solar Electric Vehicles in real-time. Tests show that the appliance can read the voltage, current, and power generated by 5 solar panels assembled in series with a total power of 500Wp. The highest rated voltage data is 73.12Volts at 14.00, while the lowest data is 65.22Volts at 17.00, the rated highest rated current is 7.11A at 12.00, while the lowest current is 1.10A at 17.00, the highest rated power is 505.65Watt at 13.00, while the lowest power is 71.74 Watts.